2017
DOI: 10.1075/ahs.7.08kai
|View full text |Cite
|
Sign up to set email alerts
|

“A graphic system which leads its own linguistic life”?

Abstract: Traditional accounts of the history of English spelling are primarily based on printed texts. According to them, English orthography developed from great diversity in Late Middle English to modern standard spelling by 1800. Studies have also revealed a split between public and private spelling practices. This paper charts the history of epistolary spelling in Early Modern English using the Corpus of Early English Correspondence. We counter potential editorial interference in the corpus by two methods. First, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The compilers used original-spelling editions to ensure that the linguistic content would be reliable for morphosyntactic studies, but even these editions frequently normalise features such as u/v variation, capitalisation or punctuation. Recent work has shown that the CEEC compilers' reservations towards using the corpora to study spelling, capitalisation, punctuation or word division were largely warranted (Sairio et al 2018; but see Kaislaniemi et al 2017). In any case, the original (editorial) spelling is preserved in the original version of the corpus, so with access to both versions, users are still able to check the spelling, albeit with some difficulty (see Section 4.2 below).…”
Section: Normalisationmentioning
confidence: 99%
“…The compilers used original-spelling editions to ensure that the linguistic content would be reliable for morphosyntactic studies, but even these editions frequently normalise features such as u/v variation, capitalisation or punctuation. Recent work has shown that the CEEC compilers' reservations towards using the corpora to study spelling, capitalisation, punctuation or word division were largely warranted (Sairio et al 2018; but see Kaislaniemi et al 2017). In any case, the original (editorial) spelling is preserved in the original version of the corpus, so with access to both versions, users are still able to check the spelling, albeit with some difficulty (see Section 4.2 below).…”
Section: Normalisationmentioning
confidence: 99%
“…Kaislaniemi et al find evidence of generational change in epistolary spellings in the Corpus of Early English Correspondence, although this sits alongside considerable "noise" and idiosyncratic variation. 28 Nevalainen suggests that the invariant spellings of some words, particularly native vocabulary, indicate that writing communities agreed on a particular spelling at a fairly early date, achieved through a process of lexical diffusion. This 'relative consensus', or convergence, around a particular graphemic form, impedes later top-down reformist attempts to reconfigure English spelling on wholly phonemic principles.…”
Section: Early Modern Spellingmentioning
confidence: 99%
“…If so, Elizabeth's spelling stabilised, despite the continuing regularisation in subsequent printed works, supporting observations that generational change is a relevant factor for manuscript spelling in the period. 84 Elizabeth's preferences also hint at inter-personal influence. Although fairly common in EEBO-TCP, the only other user of <receaue> in PCEEC is Robert Dudley, Earl of Leicester, a life-long friend and councillor.…”
Section: Idiosyncratic Spellingsmentioning
confidence: 99%